Análisis de los resultados en la implementación del sistema inicial de gestión organizacional (SIGO) en MIPYMES de San Miguel de los Bancos - Mindo, durante el periodo 2014-2015 - Coronel Arévalo, Jenniffer Estefanía (2016)
This work establishes a case of study based on the implementation of the Initial Organizational Management System in the location of Mindo, San Miguel de los Bancos. This study identifies the process of implementing the system, measures the results obtained in the process and analyzes the level of implementation of the establishments, articulated to the initiative, one year later. The document contains a theoretical approach that allows the readers to expand their knowledge in function of; quality in the world, principles of quality, standards and certification function, quality tourism, management systems and the SIGO Ecuador. As part of the study a research methodology was implemented, which includes the design and adaptation of monitoring tools, same that were used during the field research. Also, interviews with experts were developed, in order to verify the information and make a triangular analysis of obtained data, classifying the information by different stages such as; diagnosis, final verification and monitoring. Thanks to all above, the level of evolution of the different establishments that were part of the process was identified. Also, it was established the main strengths of the implementation phase, as well as critical reflection that will be useful for future implementations in other territories. It is important to mention the positive effect achieved by the establishments, which allows a first approach to an implementation model of quality, according to the country reality. It is therefore necessary to point out that in the case of Ecuador, this was the first year of implementation of a management system, applied from the central public sector. Moreover, other experiences of private initiative, as the distinctive Q or Smart Voyager, were implemented in recent years.